Monofunctional Cities: Problems, Support Provision and Development - Kuzmenko, L.M.; Soldak, M.O. (Економічний вісник Донбасу, 2010)
The paper considers the peculiarities of industry in the monoindustrial cities in Donetsk region. The actions for solving the problems of the social and economic development are proposed here. Key words: monofunctional (monoindustrial) city, development, industry, state management, regional policy.